Histochemical studies of liver in buffalo (Bubalus bubalis): Histochemical studies of liver in buffalo (Bubalus bubalis) - Thakur, Pravin Narayan (Buffalo Bulletin, 2020)
The gross histochemical studies of the 24 buffaloes livers (12 male and 12 female) were carried out. PAS reaction was intense in hepatocytes in all regions of liver in male and female except apex of caudate lobe in female where it was weak and below the portal vein in male which was intense. The other components showed moderate to weak reaction in both male and female buffaloes. Alkaline phosphatase reaction was weak in hepatocytes in all the regions of liver of male and female buffalo except upper third of parietal surface and below the portal vein in female, while other components showed weak to negative reaction in both male female buffaloes. Acid phosphatase reaction was moderate in hepatocytes in neck of gall bladder in both the sex and apex of caudate lobe in male, while moderate to negative reaction in other components of male and female. Ferric iron granules were present in the cytoplasm of hepatocytes of both male and female, which were pale blue in colouration.